2004
DOI: 10.1523/jneurosci.5491-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Memory Reconsolidation and Extinction Have Distinct Temporal and Biochemical Signatures

Abstract: Memory retrieval is not a passive phenomenon. Instead, it triggers a number of processes that either reinforce or alter stored information. Retrieval is thought to activate a second memory consolidation cascade (reconsolidation) that requires protein synthesis. Here, we show that the temporal dynamics of memory reconsolidation are dependent on the strength and age of the memory, such that younger and weaker memories are more easily reconsolidated than older and stronger memories. We also report that reconsolid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

116
1,129
7
13

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,036 publications
(1,265 citation statements)
references
References 66 publications
116
1,129
7
13
Order By: Relevance
“…However this interpretation is somewhat limited by the fact that SR141716 given alone delayed extinction. As previously described in a similar water maze task (Varvel et al, 2005a) and in conditioned fear paradigms (Marsicano et al, 2002;Suzuki et al, 2004;Chhatwal et al, 2005), SR141716 robustly attenuated extinction in the present experiment. The effect of SR141716 presented here replicates our previously published report, with some minor procedural differences such as the weekly extinction trials (as opposed to bi-weekly trials) and the inclusion of the quadrant data.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However this interpretation is somewhat limited by the fact that SR141716 given alone delayed extinction. As previously described in a similar water maze task (Varvel et al, 2005a) and in conditioned fear paradigms (Marsicano et al, 2002;Suzuki et al, 2004;Chhatwal et al, 2005), SR141716 robustly attenuated extinction in the present experiment. The effect of SR141716 presented here replicates our previously published report, with some minor procedural differences such as the weekly extinction trials (as opposed to bi-weekly trials) and the inclusion of the quadrant data.…”
Section: Discussionsupporting
confidence: 88%
“…These findings support the hypothesis that the endocannabinoid system plays an important role in modulating extinction learning (Marsicano et al, 2002;Suzuki et al, 2004;Varvel et al, 2005a). In contrast, a wide dose range of THC failed to have any significant effects on extinction.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Briefly, fear memories, when reactivated by re-exposure (retrieval), enter into a labile state in which the memory trace may either be reconsolidated or extinguished [97], and this process may be pharmacologically modulated to achieve reconsolidation blockade or extinction. When administered immediately following retrieval, CBD prevented freezing to the conditioned context upon further re-exposure, and no reinstatement or spontaneous recovery was observed over 3 weeks, consistent with reconsolidation blockade rather than extinction [76].…”
Section: Contextual Fear Conditioning Fear Extinction and Reconsolimentioning
confidence: 99%
“…Given the role of NMDARs in the induction of synaptic plasticity (Martin et al, 2000;Riedel et al, 2003), the most likely interpretation of these results is that the synaptic plasticity required for the acquisition of fear extinction was disrupted. However, two studies (Santini et al, 2001;Suzuki et al, 2004), using a different measure of fear (freezing rather than potentiated startle) and systemic infusions of the non-subunit selective NMDAR antagonist CPP ((7)-3-(2-carboxypiperazin-4-yl)-propyl-1-phosphonic acid), found that whereas the retention of extinction was impaired, there was no apparent impairment during the acquisition of extinction.…”
Section: Introductionmentioning
confidence: 99%